What is a transition? Exploring visual and textual definitions among sustainability transition networks. (May 2018) - Silva, Angie; Stocker, Laura
Highlights: Transition is defined both textually and visually using the draw and write technique. Comparative definitions are presented by Sustainability Transition Research Network and Transition Towns community. The findings show transition is being interpreted and defined from different worldviews. Transition networks defined transition as either a process or a desired sustainability outcome. An opportunity to encompass both processes and outcomes can enhance transitions in future. Abstract: 'What is a transition?' This question is pertinent in understanding the motivation amongst scientists, policy makers, practitioners, business actors and community groups in transitioning society towards sustainability. The Sustainability Transition Research Network and Transition Towns have emerged as two highly visible global networks, shaping and legitimising how transitions are interpreted and implemented. This ability to narrate and frame the 'transition concept' is significant in determining sustainability transitions in future. Yet, previous studies have not comparatively explored how transition knowledge is understood and defined both visually and textually by members belonging to these two global networks. Employing an innovative visual data collection methodology (the draw and write technique), we compare and contrast both the textual and visual representations of a transition across the two networks. The results suggest that there are some differences in worldviews between the two networks; however potential synergies between the two networks could promote a more comprehensive understanding of transitions, which better accounts for all aspects of social and technological change towards sustainability.